Gauge group contraction of electroweak model and its natural energy limits - Nikolay A Gromov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2015)
The low and higher energy limits of the Electroweak Model are obtained from ﬁrst principles of gauge theory. Both limits are given by the same contraction of the gauge group, but for the diﬀerent consistent rescalings of the ﬁeld space. Mathematical contraction parameter in both cases is interpreted as energy. The very weak neutrino-matter interaction is explained by zero tending contraction parameter, which depends on neutrino energy. The second consistent rescaling corresponds to the higher energy limit of the Electroweak Model. At the inﬁnite energy all particles lose masses, electroweak interactions become long-range and are mediated by the neutral currents. The limit model represents the development of the early Universe from the Big Bang up to the end of the ﬁrst second.